Eltrombopag to Treat Thrombocytopenia During Last Month of Pregnancy in a Woman With MYH9-Related Disease: A Case Report. Issue 1 (1st January 2018) - Favier, Remi; De Carne, Celine; Elefant, Elisabeth; Lapusneanu, Ruxanda; Gkalea, Vasiliki; Rigouzzo, Agnès
Abstract : MYH9-related disease (MYH9-RD) is an inherited rare autosomal dominant macrothrombocytopenia. Patients with MYH9-RD have giant platelets and leukocyte inclusion bodies caused by mutations in the MYH9 gene encoding the non–muscle myosin heavy chain II-A. Before identification of the causative gene, patients were diagnosed as Epstein or Fechtner or Sebastian syndromes or May-Hegglin anomaly. As with other inherited thrombocytopenias, the risk of increased bleeding during perioperative period or delivery is a major concern. We report here the first successful cesarean delivery of a woman with MYH9-RD treated with eltrombopag during the last month of pregnancy.